2017
DOI: 10.1016/j.jcin.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Warfarin Therapy for Bioprosthetic Valve Thrombosis of Surgically Implanted Valves

Abstract: A trial of anticoagulation was effective in 83% of patients with suspected BPVT, and most patients responded within 3 months. BPVT score was predictive of response to therapy and should be considered during patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 16 publications
2
34
0
4
Order By: Relevance
“…Egbe et al 30 performed a prospective trial of anticoagulation with warfarin (target international normalised ratio 2 to 3) in patients with suspected bioprosthetic valve thrombosis. This strategy reduced valve gradients in 83% of the cohort (response defined as 50% reduction in valve gradient) within a median time of 11 weeks.…”
Section: Managementmentioning
confidence: 99%
“…Egbe et al 30 performed a prospective trial of anticoagulation with warfarin (target international normalised ratio 2 to 3) in patients with suspected bioprosthetic valve thrombosis. This strategy reduced valve gradients in 83% of the cohort (response defined as 50% reduction in valve gradient) within a median time of 11 weeks.…”
Section: Managementmentioning
confidence: 99%
“…Several studies have reported successful resolution of BPVT when treated with VKA (vitamin K antagonist) 5678 . A prospective evaluation of warfarin showed that anticoagulation was effective in 83% of patients with suspected BPVT, and most responded within 3 months 7 . A recent study by Petrescu et al reported long term outcomes of anticoagulation in 83 patients treated with warfarin for suspected BPVT.…”
Section: Discussionmentioning
confidence: 99%
“…1 In a prospective trial of 52 patients with suspected BPVT, warfarin therapy for 3 months reduced the prosthesis gradient by at least half in 83% of the patients. 4 Echocardiography is a key tool for diagnosing prosthetic valve stenosis; however, guidelines state that routine monitoring of bioprosthetic valves by means of annual TTE should begin 10 years after implantation. 5 Some investigators have called for annual TTE screening 2,6 because the peak incidence of BPVT may occur during the first 1 to 2 years after valve implantation.…”
Section: Discussionmentioning
confidence: 99%